Project SOARS: Student Ownership, Accountability, and Responsibility for School Safety, Illinois and Oregon, 2016-2020 - Pennefather, Jordan ([Verlag nicht ermittelbar], 2024)
Project SOARS (Student Ownership, Accountability, and Responsibility for School Safety) utilized a mixed-methods study design to develop and test a student-centered and technology-driven school safety framework to address peer victimization, violent behavior, and student reluctance to share critical safety information within high school settings. SOARS was a project of IRIS Media, Inc. and consisted of 4 phases implemented between 2016 and 2020. Activities for each phase were carried out in Oregon and Illinois high schools in order to facilitate inter-site replication of outcomes. Phase 1 was conducted in 2016 and consisted of focus groups and key informant interviews with students, school personnel, and parents to gather perceptions of current school safety practices. Phase 2 was undertaken in 2017 and asked students, school personnel, and parents to assess the acceptability and usability of prototypes of the SOARS framework. The SOARS framework consisted of (a) the Advocatr mobile app, which allowed students to report positive and negative behaviors in their school environment; (b) a 9-week curriculum engaging students with the concepts of student ownership of school safety, advocacy/self-advocacy, physical and emotional safety, and restorative conflict resolution; (c) informational briefs for school personnel and parents about the framework components and their rationale; and (d) guidelines for a student-led school-wide safety campaign. Phase 3 was rolled out in 2018 and 2019 and consisted of feasibility testing conducted with a small subset of teachers and students in those teachers' classrooms. Participants were surveyed before and after implementation of the SOARS framework. The focus of the feasibility test was on student access and use of the Advocatr app and the accompanying curriculum. During Phase 4 implementation in 2019 and 2020, researchers conducted a pilot test with students, school personnel, and parents from 4 high schools, 2 assigned to the intervention and 2 to the control condition. The focus of the pilot was to test the effectiveness of the SOARS framework. Demographic information was collected from all informants and includes gender (sex male or female; transgender identification), ethnicity, and race. Additional demographic information about students includes sexual orientation, approximate age (over/under 18 years), primary language, GPA, and grade. Parent demographics also include education level and student's grade, while school personnel (teachers and staff) also provided information regarding education level, school role, job title, years in current position, grades taught, and subjects taught. Users should note that qualitative data collected during phase 1 focus groups and phase 2 user acceptance tests are not included in version 1 of the ICPSR release. Additionally, in the quantitative datasets, character variables featuring open-ended string responses have been masked by ICPSR. This study will be updated at a later date to include qualitative data files and character variables in the quantitative datasets.